2022
DOI: 10.1111/avj.13214
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐professional stress—demonstrating veterinarian identity in Hong Kong

Abstract: Objective Little is known about the contributing factors of mental health among veterinarians in Hong Kong. This qualitative study aimed to examine potential contributing factors that lead to their stress and poor mental health. Procedures Potential participants were screened and recruited using purposive and snowball sampling to maximise variations. Semi‐structured interviews were conducted between December 2020 and April 2021. The data collection and analysis adopted the constructivist grounded theory's thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…Moreover, they city's lack of business regulatory requirements for the profession challenges veterinarian-employees and, possibly, the welfare of animals. 13 Besides the limited legal liability for medical misconduct on non-veterinarian investors, 13 businessmen-owned veterinary clinics are believed less familiarised with the speci city of ethics in veterinary medicine, such as the appropriate length of medical consultation and a fair-minded pro t model of the veterinary enterprises. 13 Our previous qualitative study found that veterinarians' experience of workplace leadership and workplace harmony were some factors affecting their mental health.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, they city's lack of business regulatory requirements for the profession challenges veterinarian-employees and, possibly, the welfare of animals. 13 Besides the limited legal liability for medical misconduct on non-veterinarian investors, 13 businessmen-owned veterinary clinics are believed less familiarised with the speci city of ethics in veterinary medicine, such as the appropriate length of medical consultation and a fair-minded pro t model of the veterinary enterprises. 13 Our previous qualitative study found that veterinarians' experience of workplace leadership and workplace harmony were some factors affecting their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…13 Besides the limited legal liability for medical misconduct on non-veterinarian investors, 13 businessmen-owned veterinary clinics are believed less familiarised with the speci city of ethics in veterinary medicine, such as the appropriate length of medical consultation and a fair-minded pro t model of the veterinary enterprises. 13 Our previous qualitative study found that veterinarians' experience of workplace leadership and workplace harmony were some factors affecting their mental health. 13 The main barriers to accessing mental health services was due to their lack of work-life balance, resulted from their late nishing and unpredictable work schedule.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations